Material Cultures of Early Modern Women's Writing
XIII, 214 p.
Keywords: This collection examines the diverse material cultures through which early modern women's writing was produced, transmitted, and received. It focuses on the ways it was originally packaged and promoted, how it circulated in its contemporary contexts, and how it was read and received in its original publication and in later revisions and redactions.